2018
DOI: 10.1155/2018/3646725
|View full text |Cite
|
Sign up to set email alerts
|

Ceramide and Ischemia/Reperfusion Injury

Abstract: Ceramide, a bioactive membrane sphingolipid, functions as an important second messenger in apoptosis and cell signaling. In response to stresses, it may be generated by de novo synthesis, sphingomyelin hydrolysis, and/or recycling of complex sphingolipids. It is cleared from cells through the activity of ceramidases, phosphorylation to ceramide-1-phosphate, or resynthesis into more complex sphingolipids. Ischemia/reperfusion (IR) injury occurs when oxygen/nutrition is rapidly reintroduced into ischemic tissue,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
29
0

Year Published

2018
2018
2020
2020

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 99 publications
0
29
0
Order By: Relevance
“…The ability of ROS to activate different ceramide generating pathways has been extensively studied in many cell types [52,53,54,55]. Thus, a number of reports have indicated that the generation of ROS in response to various stimuli such as antileukemic agents [56], stress [57], ischemia-reperfusion [58], pathogens [59], or hypoxia [26,27] may lead to ceramide accumulation. Both nSMase and aSMase are redox-sensitive enzymes whose activities are incremented by ROS [51,53,55].…”
Section: Ceramide and Redox Signalingmentioning
confidence: 99%
“…The ability of ROS to activate different ceramide generating pathways has been extensively studied in many cell types [52,53,54,55]. Thus, a number of reports have indicated that the generation of ROS in response to various stimuli such as antileukemic agents [56], stress [57], ischemia-reperfusion [58], pathogens [59], or hypoxia [26,27] may lead to ceramide accumulation. Both nSMase and aSMase are redox-sensitive enzymes whose activities are incremented by ROS [51,53,55].…”
Section: Ceramide and Redox Signalingmentioning
confidence: 99%
“…The role of mitochondria in cell death signaling by ceramide has been reviewed extensively [ 247 , 248 ]. However, evidence is accumulating on ceramide roles in a whole spectrum of regulatory events that affect their function.…”
Section: Bioactive Sphingolipids In Agingmentioning
confidence: 99%
“…Ceramide is a central lipid component of sphingolipid structure that is biosynthesized by three pathways, which include de novo synthesis from palmitoyl-CoA and serine, hydrolysis of sphingomyelin or a salvage pathway 17 . It is an important lipid mediator regulating various cellular responses like cell death, and recent evidence also suggests a role in various metabolic pathways influencing mitochondrial function 18 . In vitro data indicate production of ceramide increases in glycolytic cells but decreases in cells with developed OXPHOS 19 .…”
Section: Introductionmentioning
confidence: 99%